Mathematics Critical Thinking Ability Based on Student’s Cognitive Style in Whole Brain Teaching in Ethnomathematics - Rahayu, Uswatun Khasanah Dwi; Zaenuri, Zaenuri; Walid, Walid (Universitas Negeri Semarang, 2019)
This research is aimed to (1) investigate the effectiveness of student learning in the application of the Whole Brain Teaching in ethnomathematic in improving mathematics critical thinking ability, and (2) explain the mathematics critical thinking ability in the application of Whole Brain Teaching in ethnomathematic in terms of student’s cognitive style. Mixed method with sequential explanatory was applied in this research. Critical Thinking Ability Test, observation, and interview were employed in obtaining the data. Selection of research subjects were according to cognitive by using GEFT. The data analysis appeared to prove that (1) WBT learning model in ethnomathematic effective to the achievement of student’s mathematics critical thinking ability, and (2) the achievement of student’s mathematics critical thinking ability of FD were capable and fluent in three indicators, FIL student capable and fulfill four indicators, and FIK student capable and fulfill all the indicators. Based on this research, the WBT model in ethnomathematic can be choice to improve student’s learning outcomes, particularly the mathematics critical thinking ability. Student interest in local culture will facilitate the understanding of the learning material.